Linguistic and Philosophical Aspects of the Symbol (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The particular properties of symbols are discussed in this article. The cases of relaxation in linguistic and speech phenomena, which demonstrate the speech culture, language richness, and human behavior, are also highlighted in conjunction with the analysis of the linguistic nature of the symbols. These cases help to guarantee the diversity and efficacy of the speech. Simultaneously, the views of numerous scientists and philosophers regarding the symbol that emerged from examining the research projects were regarded as facts.